The intangible benefits of criminal mentorship - Ouellet, Frédéric (The criminology of Carlo Morselli ; part 2, 2024)
Individuals who report having had a mentor also tend to report higher levels of criminal achievement. However, prior studies focused on indirect yet tangible outcomes of mentorship, telling us little about the direct – though potentially intangible – benefits of these relationships to the mentee. In this study, we analyse the content of 28 life story narratives of offenders to examine the effects of mentor-mentee relationships. Half of the participants reported having had a mentor, but many did not meet our definition of mentorship that emphasised direct support in the context of criminal activities. Instead, participants described many intangible benefits of mentorship that we classified in two general categories: benefits to one’s criminal capital (high-level career advice, practical skills), and benefits to one’s social capital, in the form of either criminal partnership, an enhancement to one’s reputation or protection, or providing mentees with the independence necessary to succeed on their own.